PD-1/PD-L1 inhibitors related adverse events: A bibliometric analysis from 2014 to 2024 - Qingya Song; Zongliang Yu; Wenping Lu; Zhili Zhuo; Lei Chang; Heting Mei; Yongjia Cui; Dongni Zhang (Human Vaccines & Immunotherapeutics)
Programmed cell death-1 (PD-1) inhibitors and programmed cell death ligand 1 (PD-L1) inhibitors are considered effective alternatives for the primary treatment of recurrent metastatic cancers. However, they can induce various adverse events affecting multiple organ systems, potentially diminishing patients’ quality of life, and even leading to treatment interruptions. Adverse events related to PD-1/PD-L1 inhibitors differ from those associated with CTLA-4 inhibitors and are more commonly observed in the treatment of solid tumors. This study aimed to address the knowledge gap regarding adverse events related to PD-1/PD-L1 inhibitors. A visual bibliometric network was constructed using VOSviewer, CiteSpace, R software, and the Web of Science Core Collection (WoSCC) to quantitatively analyze this research field. Future research directions were also explored. The USA ranked first in publication count and total citations. Over time, publication types transitioned from case reports to clinical trials. Research on for nivolumab was the most prevalent. The spectrum of cancers treated by PD-1/PD-L1 inhibitors expanded beyond melanoma and lung cancer to include renal cell carcinoma, esophageal cancer, and others. Common adverse events included pneumonitis, myasthenia gravis, and vitiligo. There was a significant increase in multi-phase clinical trials and studies related to biomarkers. This study offers valuable insights for potential collaborators and institutions, highlighting trends in the study of adverse events related to PD-1/PD-L1 inhibitors. The management of these adverse events has become more refined and standardized. Biomarker research and multi-phase clinical trials are likely to be key areas of focus in future studies.